Soil microbial CO2 fixation rate disparities with different vegetation at a representative acidic red soil experimental station in China - Long, Chao; Liu, Zuwen; Liu, Renlu; Yin, Li; Tan, Fuxing; Wang, Yian; He, Genhe (Frontiers in Microbiology, 2024)
Soil acidification poses a significant environmental challenge in China’s southern red soil regions, impacting the abundance of soil microbes and their capacity for carbon fixation. The effect of vegetation types on soil’s biological and abiotic components under acidification, and their regulatory role on the CO2 fixation mechanisms of soil autotrophic microorganisms, is difficult to examine. This gap in understanding constrains the assessment of the carbon fixation potential of red soils. To address this, indoor cultivation coupled with 13C stable isotope labeling was employed to evaluate the disparate abilities of autotrophic microorganisms to assimilate and store CO2 across five vegetation soils from the Qianyanzhou acidic red soil experimental station in China. Findings indicate that carbon fixation rates in these soils spanned from 4.25 to 18.15 mg C kg−1 soil d−1, with paddy field soils demonstrating superior carbon fixation capabilities compared to orchard, coniferous forest, broad-leaved forest, and wasteland soils. The 13C fixation rate in the 0–10 cm soil stratum surpassed that of the 10–30 cm layer across all vegetation types. High-throughput sequencing of 16S rRNA, following cbbL gene purification and amplification, identified Bradyrhizobium, Azospirillum, Burkholderia, Paraburkholderia, and Thermomonospora as the predominant autotrophic carbon-fixing microbial genera in the soil. PERMANOVA analysis attributed 65.72% of the variance in microbial community composition to vegetation type, while soil depth accounted for a mere 8.58%. Network analysis of microbial co-occurrence suggested the soil microbial interactions and network complexity changed with the change of vegetation types. Additionally, multiple linear regression analysis pinpointed the Shannon index and soil organic carbon (SOC) content as primary influencers of carbon fixation rates. Structural equation modeling suggested that iron enrichment and acidification indirectly modulated carbon fixation rates by altering SOC and autotrophic bacterial diversity. This investigation shows the spatial dynamics and mechanisms underpinning microbial carbon fixation across varying vegetation types in southern China’s red soil regions.